PENGARUH BOBOT DAN FREKUENSI PEMUTARAN TERHADAP FERLITAS, DAYA TETAS DAN BOBOT TETAS ITIK JAWA LOKAL - Hamanay, Febrianto Lu; Handayani, Sri; Fitasari, Eka (Universitas Tribhuwana Tunggadewi, 2019)
This study aims to obtain egg weight in grams (g) and the frequency of playback of local javanese duck eggs that are ideal in hatching local javanese duck eggs. The design used was a completely randomized design (RAL) factorial pattern, consisting of 3 treatments and 3 replications. Each treatment received 3 replications. The treatments tested were : the first factor is the egg weight of hatching eggs with notation ( B ), namely : B1= 53 g – 60 g, B2= 61g – 68 g, and B3= 69 g – 76 g. The second factor is the frequency of egg playback with notation ( p ) which is p1= 3x a day, p2= 4x a day, p3= 6x a day. The results showed that egg weight and playback frequency had no significant effect on fertility, hatchability, and hatch weight ( p